Image stitching method by multi‐feature constrained alignment and colour adjustment. Issue 7 (7th January 2021) - Yuan, Xingsheng; Zheng, Yongbin; Zhao, Wei; Su, Jiongming; Wu, Jianzhai
Abstract: Image alignment and colour consistency are two challenging tasks for image stitching. Traditional point correspondence methods are difficult to achieve good alignments due to their insufficiency and unreliability. The results are prone to errors and distortions. On the other hand, the problem of colour inconsistency in overlapping area between image pairs is still difficult to solve, especially when the illumination difference between images is large. To solve these problems, the authors integrate point features and line features into a warping model through a designed energy function. Line features will provide geometric constraints for image stitching, and remedy the defect of point correspondences in low‐textured image stitching. A global colour consistency optimization method with colour mapping via a histogram extreme point‐matching algorithm is proposed. The colour characteristic of reference images will be transferred to the others to achieve a global colour consistency. The proposed method is evaluated on a series of images, and compared with other methods. The experiments demonstrate that the proposed method provides convincing stitching results and achieves satisfied colour consistency results.